2019
DOI: 10.3390/su11185021
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Relationship between Worker States and Unsafe Behaviours in Coal Mine Accidents Based on a Bayesian Networks Model

Abstract: Unsafe behaviours, such as violations of rules and procedures, are commonly identified as important causal factors in coal mine accidents. Meanwhile, a recurring conclusion of accident investigations is that worker states, such as mental fatigue, illness, physiological fatigue, etc., are important contributory factors to unsafe behaviour. In this article, we seek to provide a quantitative analysis on the relationship between the worker state and unsafe behaviours in coal mine accidents, based on a case study d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
(43 reference statements)
1
11
0
1
Order By: Relevance
“…In addition, it clarifies the mechanism of risk factors on unsafe acts. Therefore, our findings provide a starting point for more detailed research in the future ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 67%
“…In addition, it clarifies the mechanism of risk factors on unsafe acts. Therefore, our findings provide a starting point for more detailed research in the future ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 67%
“…In addition, Gracia and MartĂ­nez-CĂłrcoles found that role stress can lead to workplace risky behaviors and trigger safety accidents among employees [ 24 ]. Accident investigations have shown that worker states are essential factors contributing to unsafe behaviors [ 25 ]. Nasab et al first discussed the evolution of unsafe behaviors in workers’ operating processes through factors such as workers’ attitudes, job involvement, job satisfaction, and organizational commitment [ 26 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Seo et al (14) identified that personal characteristics have an indirect influence on safety behavior. Chen et al (17)(18)(19) also reported that individual characteristics, such as gender, age, education level, and working years, have a significant impact on employees' behaviors: inexperienced and younger coal miners are more likely to engage in unsafe behavior. In contrast, Malakoutikhah et al (35) asserted that workers' age, education level, work experience, and years of study had no influence on their unsafe behavior.…”
Section: Individual Factorsmentioning
confidence: 99%